2010
DOI: 10.1177/0022034510377203
|View full text |Cite
|
Sign up to set email alerts
|

Subgingival Microbial Profiles of Smokers with Periodontitis

Abstract: The subgingival microbiome is largely uncultivated, and therefore, cultivation-based and targeted molecular approaches have limited value in examining the effect of smoking on this community. We tested the hypothesis that the subgingival biofilm is compositionally different in current and never-smokers by using an open-ended molecular approach for bacterial identification. Subgingival plaque from deep sites of current and never-smokers matched for disease was analyzed by 16S sequencing. Smokers demonstrated gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
218
1
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(247 citation statements)
references
References 34 publications
12
218
1
11
Order By: Relevance
“…16,17,18,19,20 However, other authors have not found this association. 21,22,23 It has also been shown that smokers have less favorable responses to non-surgical and surgical periodontal therapy than nonsmokers.…”
mentioning
confidence: 90%
“…16,17,18,19,20 However, other authors have not found this association. 21,22,23 It has also been shown that smokers have less favorable responses to non-surgical and surgical periodontal therapy than nonsmokers.…”
mentioning
confidence: 90%
“…Studies have found alterations in the oral microbiome in smokers compared with nonsmokers, with increases in some species and decreases in others (45,46). A recent study from the Lung HIV Microbiome Program found that oral microbial composition differed significantly by smoking status, but BAL communities in smokers and nonsmokers…”
Section: The Role Of Smokingmentioning
confidence: 99%
“…The polymerase chain reaction (PCR) is a more sensitive and specific method for the detection of bacteria than conventional culture-based methods. A series of recent studies (Preshaw et al, 2005b;Delima et al, 2010;Shchipkova et al, 2010) revealed a bacteriological mechanism by using a novel method for bacterial identification. The microbial profile of disease-associated and health-compatible organisms in smokingassociated periodontitis patients was significantly different from that in non-smokers.…”
Section: Biological Plausibilitymentioning
confidence: 99%